Decrease of disease‐related metabolites upon fasting in a hemizygous knock‐in mouse model (Mut‐ko/ki) of methylmalonic aciduria. Issue 1 (8th November 2020) - Lucienne, Marie; Mathis, Déborah; Perkins, Nathan; Fingerhut, Ralph; Baumgartner, Matthias R.; Froese, D. Sean
Abstract: Methylmalonyl‐CoA mutase (MMUT) is part of the propionyl‐CoA catabolic pathway, responsible for the breakdown of branched‐chain amino acids, odd‐chain fatty acids and the side‐chain of cholesterol. Patients with deficient activity of MMUT suffer from isolated methylmalonic aciduria (MMAuria), frequently presenting in the newborn period with failure to thrive and metabolic crisis. Even well managed patients remain at risk for metabolic crises, of which one known trigger is acute illness, which may lead to poor feeding and vomiting, putting the patient in a catabolic state. This situation is believed to result in increased breakdown of propionyl‐CoA catabolic pathway precursors, producing massively elevated levels of disease related metabolites, including methylmalonic acid and propionylcarnitine. Here, we used fasting of a hemizygous mouse model ( Mut ‐ko/ki) of MMUT deficiency to study the role of induced catabolism on metabolite production. Although mice lost weight and displayed markers consistent with a catabolic state, contrary to expectation, we found strongly reduced levels of methylmalonic acid and propionylcarnitine in fasted conditions. Switching Mut ‐ko/ki mice from a high‐protein diet to fasted conditions, or from a standard diet to a no‐protein diet, resulted in similar reductions of methylmalonic acid and propionylcarnitine levels. These results suggest, in our mouse model at least, induction of a catabolic state on its own may not be sufficient to trigger elevated metabolite levels.